Upaya Meningkatkan Motivasi dan Hasil Belajar PAI & BP Materi Iman Kepada Kitab-Kitab Allah Melalui Penerapan Model Pembelajaran The Power Of Two Siswa Kelas 8.B SMP Negeri 26 BATAM - Eva Sekreyenti (STIKes Ibnu Sina Ajibarang, 2023)
This research is an effort to increase student motivation and learning outcomes using The Power of Two method in Class 8.B students at SMP Negeri 26 Batam. The type of research is classroom action research. The steps in this classroom action research are planning, implementation, observation and reflection which are carried out in two cycles. The subjects in this research were students in Class 8.B of SMP Negeri 26 Batam Semester 1 of the 2022/2023 academic year, totaling 35 students. Data collection was carried out using observation, test and documentation techniques. The data collected is in the form of observations, tests and learning documentation. Data validation in this action research is democratic, process and dialogic validity. The data obtained was analyzed descriptively. The research results showed that learning completeness before learning improvements were carried out was 22.86% or 8 students, in the first cycle it was 18 students or 51.43% and in the last cycle it was 33 students or 94.29%. The conclusion is that the application of The Power of Two Method is proven to be able to increase student motivation and learning outcomes in learning Islamic Religious Education and Character for Class 8.B Students of SMP Negeri 26 Batam Semester 1 of the 2022/2023 Academic Year.